Penggunaan Platform Video Pendek Sebagai Strategi Komunikasi Pemasaran Digital untuk UMKM - Miftahul Rozaq; Rah Utami Nugrahani (Jurnal Komunikasi Nusantara, 2023)
The short video platform via social media has become very popular in Indonesia and is one of the main tools for strategic communication for entrepreneurs. However, research regarding the use of short video platforms as a strategic communication tool for entrepreneurship is still limited and has not been discussed in depth. This study aims to identify and classify various uses of short video platforms as strategic communication tools for entrepreneurship. This research was conducted using a qualitative approach using a descriptive case study method with 12 entrepreneurs on the island of Java, Indonesia. In-depth interviews and observations were conducted to examine the use of short video platforms and communication strategies used by entrepreneurs. The results of the study show that the use of short video platforms by entrepreneurs includes; following viral content, using music features, educational content, and live streaming. While the communication strategies used include; entertainment and humor, sharing information and promotions, co-branding, and using people/influencer elements. Abstrak Platform video pendek buatan pengguna melalui media sosial menjadi sangat popular di Indonesia, dan menjadi salah satu alat utama untuk komunikasi strategis bagi wirausaha. Namun, penelitian terkait penggunaan platform video pendek sebagai alat komunikasi strategis untuk kewirausahaan masih terbatas dan belum dibahas secara mendalam. Penelitian ini bertujuan mengidentifikasi dan menklasifikasikan berbagai penggunaan platform video pendek sebagai alat komunikasi strategis untuk kewirausahaan. Penelitian ini dilakukan dengan pendekatan kualitatif menggunakan metode studi kasus deskriptif kepada 12 wirausaha di pulau Jawa, Indonesia. Wawancara mendalam dan observasi dilakukan untuk menkaji penggunaan platform video pendek dan strategi komunikasi yang digunakan wirausaha. Hasil penelitian menunjukkan, penggunaan platform video pendek oleh wirausaha antara lain; mengikuti konten viral, penggunaan fitur musik, konten edukasi, dan live streaming. Sedangkan strategi komunikasi yang digunakan antara lain; entertainment dan humor, membagikan informasi dan promosi, co-branding, dan penggunaan elemen orang/ influencer.